If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 5x + -6 Reorder the terms: 14 = -6 + 5x Solving 14 = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 14 + -5x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 14 + -5x = -6 + 0 14 + -5x = -6 Add '-14' to each side of the equation. 14 + -14 + -5x = -6 + -14 Combine like terms: 14 + -14 = 0 0 + -5x = -6 + -14 -5x = -6 + -14 Combine like terms: -6 + -14 = -20 -5x = -20 Divide each side by '-5'. x = 4 Simplifying x = 4
| 2x^2-7r-16=0 | | 8=x/-5+5 | | 6n+21=4n+57+2n | | Ln(n^2+12)=ln(-9n-2) | | 3k-6+2k=12+8k-33 | | -4x-18=-(4x+2) | | 3/2+3/4 | | 8+4y=12 | | 65x=55x+100 | | m-14/9=-27 | | 4k+11+2k=-5-27k-3 | | 4x+16=4(x+4) | | 11/2+3/4 | | 3=-6n-9 | | 3(4-x)-22=x+48 | | 99x^8+63x^5-45x^2= | | -3+4(-6y-2)=4(2y-1)+3 | | y-10=-1(x-4) | | -25y+25y=-(22y+15)+10+22 | | 3x-10=5x+14 | | -33k=19 | | B+(-11)=6 | | x/3+7=11 | | -2*(-8)+4y=-8 | | -12(m-4)=240 | | -2m+8=4 | | -1v-6= | | 3x(4x+5)-5(4x+5)=0 | | (5x-2)-(6-2X)=-x-9+5x | | 4-(-72/18) | | 0.5/n=2.5/4.5 | | 2x-2/4+3=6 |